Characterisation of Tetrastigma rafflesiae mitochondrial genes and assessment of their potential as sequence markers - Mohamad Hafizzudin-Fedeli,; Mohd-Faizal Abu-Bakar,; Mohd-Noor Mat-Isa,; A. Latiff,; Mohd Firdaus-Raih,; Wan, Kiew Lian (Penerbit Universiti Kebangsaan Malaysia, 2022)
Tetrastigma rafflesiae (Miq.) Planch. is a climbing plant species that is known for its unique relationship with holoparasitic plants of Rafflesiaceae. Knowledge on the mitochondrial genes of this species may contribute towards the development of molecular approaches for species identification. This study aimes to identify and characterise genes from the T. rafflesiae mitochondrial genome (mitogenome) and assess their potential to discriminate different Tetrastigma species. Mitochondrial-specific sequences were first selected by mapping T. rafflesiae whole-genome sequences to mitogenomes from several reference plant species. De novo assembly of these selected sequences produced a T. rafflesiae mitogenome with a size of 336 kb. Gene annotation revealed that the T. rafflesiae mitogenome contains at least 40 protein coding genes, 20 tRNAs and two rRNAs. Phylogenetic analysis using several mitochondrial genes, namely ccmB, cob, matR, nad6 and rps3 was able to differentiate T. rafflesiae from three other Tetrastigma species, indicating the potential of these genes as species-specific sequence markers. These findings supplement additional genetic information on T. rafflesiae and may aid in the effort of species classification and conservation.